Cooperative Learning Types of Pictures and Pictures in Increasing Student Learning Activity - Munandar, Aris; Afifah, Juliana; Fitri, Desrifa (Proceeding International Conference on Religion, Science and Education, 2024)
This study aims to increase student learning activity in class VII C at Madrasah Tsanawiyah Negeri 5 Jambi City. This research is a Classroom Action Research (CAR) which is descriptive qualitative using a qualitative approach which is strengthened by a quantitative approach. The subjects of this study were students of class VII C and teachers teach subject Aqidah Akhlak at Madrasah Tsanawiyah Negeri 5 Jambi City. This research was conducted in two cycles and through 4 stages which included: (1) Planning, (2) Implementation, (3) Observation and (4) Reflection. Data obtained through observation, interviews, questionnaires, and documentation. Data analysis was carried out using qualitative analysis consisting of data collection, data reduction, data presentation, conclusions. The results of the study showed that applying the Picture and Picture Cooperative learning model can increase student learning activity in the learning process. The increase in student learning activity can be measured from each cycle, student activity in the pre- cycle student activity scores score of 2.7 with a percentage of 54% categorized as "less active" then in cycle I of 3.4 with a percentage of 68% categorized as "quite active" and student activity in cycle II was 4.2 with a percentage of 84% categorized as "active". This the results of research at Madrasah Tsanawiyah Negeri 5 Jambi City have been well achieved.